OTE-TS - a new value-added telematics service for telemedicine applications. - Karavatselou, E.I (IEEE Transactions on information technology in biomedicine)
A new telemedicine service, called the Hellenic Telecommunication Organization Telemedicine Service (OTE-TS), which addresses an open multidisciplinary group of medical care providers (users), is presented in this paper. OTE-TS is supported by the Hellenic Telecommunication Organization (OTE) and is the result of the close collaboration of engineers, medical doctors and market analysts. Its architecture provides the user with an integrated electronic working domain handling diverse types of conversational audiovisual information and medical records. It includes a stack of functions, protocols and interfaces for data acquisition, processing and display, and for the composition of dial-up multi-party cooperation schemes (synchronous or asynchronous) that are suitable for the coordination and management of high-level consulting, reporting and reviewing activities. The service provider (i.e. OTE) performs the central administration and maintenance of the service, as well as the management of medical cases and reports that are exchanged among the users. The service has been extensively tested in real-world conditions.